Sistem Pendukung Keputusan Pemiliahan Guru Terbaik Menggunakan Metode TOPSIS (Studi Kasus: SMK Swasta PABAKU Stabat) - Dewi Yohana Br Ginting (STMIK Budi Darma, 2023)
Decision Support System for Selecting the Best Teachers in PABAKU Private Vocational School Stabat uses the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method with criteria of Attendance, Attitude, Discipline, Ability to Motivate, and Responsibility. The purpose of this research is to develop a decision support system to help the school principal in selecting the best teachers. The benefits are to improve the quality of education and to help maintain the performance of qualified teachers. The research methodology includes system analysis, functional and non-functional requirements analysis, system design, system planning, and system development. The advantage of this system is that it can assist school principals in making accurate and efficient decisions, while the disadvantage is that it requires accurate and up-to-date data. It is expected that the decision support system for selecting the best teachers can improve the quality of education and maintain the performance of qualified teachers.